Reliable and secure communication using fundamental cut-sets and fundamental circuits. (2018) - Kumar, C. Pavan; Selvakumar, R.; Bhattar, Raghunadh K.
Ensuring reliability and security has been a challenge in modern communication systems. To achieve these challenges, a novel reliable and secure communication system is designed in this paper. Reliability is achieved by constructing a class of error correcting codes called concatenated kernel codes. Security in terms of source authentication is achieved from using graph nature of trellis employing techniques from graph theory namely fundamental cut-set and fundamental circuit. It has been shown that the proposed communication framework achieves the goal of reliability and security considering the channel noise and cryptanalytic attacks. The theoretical basis of the proposed framework is validated and its performance is evaluated through simulations.